Sosialisasi Pendidikan Antinarkoba dan Antikorupsi pada Generasi Muda di MtsS. Annida BIna Insani Rancabungur - Utomo, Reza Agun; Rusli, Muhammad; Hermansius, Ranap Tumpal; Karimah, Syahadah Albaqiyatul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Drugs and corruption are serious problems that affect many aspects of life, so early preventive measures are needed to prevent the impact from widening. Implementing the socialization of anti-drug and anti-corruption education aimed at the younger generation is one of the preventive measures to avert the negative impact of drugs and corruption from spreading widely among students. The socialization activity is used the sharing session method in which the facilitators provide information about the effect of drugs and the characteristics of corruption on students. This community service activity aimed to give an understanding of anti-drug and anti-corruption education to the young generations. The result of the community has been to raise awareness of the young especially among students in case of the dangers of drugs and corruption.